Analysis of Potential Electric Energy Rice Husk using Gasification Process in West Sumatera - Rizki, Maidi; Refdinal, Nazir (LPPM Universitas Andalas, 2023)
Currently, the use of fuel is increasing, it is feared that fossil fuels will run out in the near future and the national energy policy make the target of the new renewable energy to reach 23% in 2025, especially those most widely used for electricity fuel. Energy from vegetable waste is one of solution to produce new biomass energy an alternative energy to replace fossil fuels. The potential of biomass energy at Indonesian, especially in the West Sumatra area is very large, one of which is solid waste from rice husk agricultural products. In this article, use the rice husk gasification downdraft method to produce synthetic gas to internal combustion engine and coupled with electric generator. The results of rice production at West Sumatera in 2021, which is total of 1.361.769 tons of dry unhulled rice (GKG), will produce 272.353,8 tons of rice husks or about 20% of the total rice production, and mass syngas is 235.335,47 tons, the energy potential electrical 118.924,82 MWh per year. The generator can runs 216 days continuously and cost of fuel is 224.64/day vs 302.23/day a diesel engine. So fuel of biomass gasifier 34.5% more efficient compared with the diesel engine.